Pengaruh Penggunaan Kekuasaan Keahlian Terhadap Kinerja Karyawan (Suatu Studi Terhadap Karyawan Secara Individu Pada PT. PLN Wilayah VII Cabang Manado) - Soewignyo, Tonny (JBE (Journal of Business and Economics); Volume 2 No.1, 2003 JBE UNKLAB, 2003)
The effect of the usage of expertise power on the employee’s performance have been exmined. A leader with sound leadership in using his power, among others, is needed to realize qualified staff performance. The problems and objectives of this research are: (1) how to exert power by the leader to the employees in increasing the latter’s performance; (2) to determine the influence of expert power on the employee’s performance. This research is an explanatory research with the individuals as analysis unit, and the samples taken from the PT.PLN (Persero) Region VII Manado Branch. The sampling is conducted based on the stratified random sampling. The result of the research indicated that: (1) the exertion of power by the leader to increase the employee’s performance is more of the expertise power. (2) the simple linear regression analysis reveals that partially, the usage of expertise power influence the employee’s performance. Based on the research result, it is suggested that organizational practitioners be aware which use expertise power to increase the employee’s performance.